1-Year Outcomes of a Multicenter Randomized Controlled Trial of the Ankura II Thoracic Endoprosthesis for the Endovascular Treatment of Stanford Type B Aortic Dissections - Shu, Chang; He, Hao; Fu, Weiguo; Guo, Wei; Li, Ming; Xi, Erping; Guo, Shuguang; Chen, Xueming; Xiao, Zhanxiang; Yu, Shiqiang; Huang, Jianhua; Dai, Xiangchen; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The Ankura II Thoracic Stent Graft System (Lifetech, Shenzhen, China) is an evolution of the Ankura stent graft. This study reports one-year outcomes of the Ankura II Thoracic Stent Graft System for endovascular treatment of Stanford type B aortic dissections. Methods: The Ankura II Thoracic Aortic Endovascular Trial was a randomized, single-blinded, clinical trial conducted at 12 Chinese institutes. The enrolled patients diagnosed with Stanford type B aortic dissections (TBADs) were randomly assigned to the Ankura group or Ankura II group. Standard follow-up examinations were performed at 1, 6, and 12 months. Safety and efficacy data were analyzed. Results: 132 patients with TBADs were enrolled. The outcomes for the primary safety end points revealed that the Ankura II stent graft was statistically noninferior compared to the Ankura stent graft. The 1-month device-related major adverse events (1.6% vs 0%; p=0.48), 1-month all-cause mortality (1.7% vs 4.5%; p=.621), 12-month survival rate (95.2±2.7% vs 94.1±2.9%; p=.769), and major adverse event (MAE) rate (5.1% vs 4.7% at 1 month; p=0.73 and 5.8% vs 8.9% at 12 months; p=.718) of Ankura II group are all comparable to Ankura group. The two groups showed similar primary effectiveness and true lumen expansion effect, and false lumen remodeling was improved in Ankura II group (-100.0% vs. -48.5 %; p=0.08). Conclusions: The one-year outcomes from this prospective, randomized, multicenter study demonstrate that Ankura II stent graft shows comparable results to Ankura for treating TBADs, resulting in low mortality rates, MAEs and reintervention rates. Clinical trial registration number: ChiCTR-TRC-12002844